INTEGRATING PROCESS-GENRE APPROACH WITH PROJECT IBUNKA TO IMPROVE STUDENTS’ ENGLISH WRITING - Elis Homsini Maolida; Vina Aini Salsabila (University of Kuningan, 2019)
This study goes into how an integration of process-genre approach and project ibunka improves students’ English writing. Through Process-Genre approach, students put in writing essays by combining Process and Genre based writing. Meanwhile, Project Ibunka as an online collaborative writing project is deployed as a means of publishing the students’ writing to be read and commented by other students from various cultures and countries. In the context of this study, Ibunka also provides sources used to explore the topic and as a writing model. This study is a classroom action research that involved 46 university students in two classes who learned to compose English essays in three learning cycles within twelve meetings. The integration of Process-Genre and Project Ibunka is implemented in four stages: introducing and exploring theme and topics of writing, modeling and determining genre, joint writing and independent writing. In joint and independent writing, the students go through several stages of writing process such as planning, drafting, writing, revising and editing. The result of essays scoring shows average score improvement in both classes from cycle 1 to cycle 2 and cycle 3. This students’ writing improvement is also confirmed by students’ positive responses revealed from observation, questionnaire and students interview.